Flashcard as Teaching Aid: An Action Research on Students’ Vocabulary Measurement - Hidayatul Hamdiah; Taufiq Kurniawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to assess the extent of vocabulary mastery following the use of flashcards in students in the first grade of the school. The study's sample consisted of seven grades in the elementary school, and the questionnaire was administered to 15 students. The data collection for this action research involved a memorization test that served as a vocabulary achievement test. The researcher designed a lesson plan, created printable flash cards containing pictures and their meanings to help students expand their vocabulary, which is especially challenging for students in grades 1-7 at SDIT Al-Ikhlas Perbutulan and Cirebon, as they struggle to grasp the meaning of new words and memorize them. The research results showed that the mean score of the vocabulary achievement score used after the test was 80 (graph line 2), which exceeded the minimum score target (70).